Experimental investigation on particle size and launch angle distribution of lofted dust particles by electrostatic forces. Issue 3 (1st August 2021) - Orger, Necmi Cihan; Toyoda, Kazuhiro; Masui, Hirokazu; Cho, Mengu
Abstract: Electrostatic dust transportation is one of the fundamental sources for dust activity on airless planetary bodies. Even though a series of laboratory experiments have been performed to improve our understanding of the physics behind the electrostatic dust mobilization, there are several factors to investigate such as the launch angles, the lofted particle sizes, the traveling distance of the lofted grains, the initial acceleration to the launching velocities and so on. In this experimental study, an electron beam is used with 450 eV energy to produce secondary electrons to initiate lofting of the silica microspheres in the vacuum chamber, and the particle trajectories are recorded with a microscopic telescope and a high-speed camera. The dust samples are prepared as a mixture of particles with sizes from several micrometers to approximately 90.0 μ m in radius. In addition, a polyimide tape with the adhesive surface is placed around the dust sample to collect the lofted particles up to approximately 10.0 cm distance. The collected silica microspheres are studied under the microscope to measure the size variation over the distance from the dust source. The experiment results show that spherical particles and residues effortlessly reach up to 10 cm distance, whereas the fluffy dust aggregates are observed particularly near the dust sample. In addition, the analysis of trajectories shows that the dust grains accelerate rapidly to their launching velocities below 12.0 ms due to the repulsion between the neighboring dust particles. Finally, the peak of the dust launching angle distribution is determined to be around 43.5–45° from the surface normal.